Pengaruh Penggunaan Strategi Konstrutivisme terhadap Keterampilan Menulis Karangan Argumentasi - Rizana, Ririn; Asri, Yasnur; Afnita, Afnita (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
The purpose of this research is. (1) describe the argument essay writing skills without the use of constructivist strategies class X SMA Negeri 1 Lubuk Sikaping. (2) describe the argument essay writing skills using constructivist strategy of class X SMA Negeri 1 Lubuk Sikaping. (3) the effect of using constructivist strategies for essay writing skills of argumentation class X SMA Negeri 1 Lubuk Sikaping. The data of this study is the result of an argument essay writing skills test students using constructivist strategies and the test results without the use of constructivist strategies. The data sources of this study are students of class X SMA Negeri 1 Lubuk Sikaping Pasaman semester of the school year 2011/2012. Data collected using the experimental method, which aims to control or control any symptoms that appear under certain conditions, so that can know cause and effect of the symptoms that occur. The study's findings that there is an influence on the use of constructivist strategies in teaching writing argument essay.